2013
DOI: 10.5388/aon.2013.13.3.121
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing Quality of Life in Women with Breast Cancer

Abstract: 연구의 필요성유방암은

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Significant correlations between hope or hopelessness and quality of life were reported in all five studies that examined this association; hope was associated with better quality of life 42 48 and spiritual well-being, 63 while hopelessness was associated with poorer quality of life 43 and spiritual well-being. 47…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Significant correlations between hope or hopelessness and quality of life were reported in all five studies that examined this association; hope was associated with better quality of life 42 48 and spiritual well-being, 63 while hopelessness was associated with poorer quality of life 43 and spiritual well-being. 47…”
Section: Resultsmentioning
confidence: 96%
“…All four studies that examined adjustment and resilience reported significant associations; these indicated hope with psychosocial adjustment, 44 resilience 48 and post-traumatic growth, 39 and hopelessness with poorer life adjustment ability. 50 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…수술, 방사선 요법, 항암 화 학 치료, 호르몬 요법, 면역 요법 등의 의학적 치료로 인 해 생존율이 높아졌지만 [2], 치료가 끝난 후에도 유방암 생존자들은 끊임없이 신체적, 심리적, 사회적 문제들을 경험하고 있다 [3]. 상지 기능 저하, 통증 [4], 인지기능 손 상, 폐경 [5], 피로 [6], 재발에 대한 불안과 불확실성 [7]등 이 이에 해당하며, 이러한 경험들은 일상적인 삶에 부정 적인 영향을 미치고 있는 것으로 보고되고 있다 [8]. …”
unclassified